Understanding PRC Investment Statistics - Carsten A. Holz (Center for Economic Studies and ifo Institute (CESifo), 2020)
Investment statistics of the People's Republic of China are a source of many puzzles. Some investment data are of dubious quality, while the particular concepts of investment and their changing definitions over time are often poorly understood. Fixed asset investment, a remnant of the planned economy, comes with severe limitations in terms of data coverage and compilation. Detailed sector data are available, but only for a repeatedly changing subset. Gross fixed capital formation, an alternative investment measure based on the national accounts, may be more reliable but only the most aggregate data are available. The researcher or policy-maker in need of investment data encounters a veritable minefield of data issues that this paper helps navigate.
Keywords: E22; C82; O53; 330; fixed asset investment; gross fixed capital formation; newly increased fixed assets; national accounts; Chinese statistics; data falsification